Lexicon in Tradition Kuih Ashura Malay Society Nakhon Si Thammarat Thailand: an Ethnolinguistik Study - Oktavia Winda Lestari; Yuanita Widiastuti; Mohamad Jazeri; Hasan Busri (Makassar State University, 2022)
Abstract. The study of ethnolinguistics is a combination of two sciences, namely, ethnology and linguistics. The study of certain ethnic groups, certain cultures, and the intricacies of their language is ethnolinguistic studies. With the merging of knowledge, ethnolinguistics is the study of culture and language or linguistics. This study seeks to explain the form of the lexicon and the form of culture in the Kuih Ashura tradition of the Malay society of Nakhon Si Thammarat Thailand. This research is based on the study of ethnolinguistic theory which explains the relationship between culture and language. This type of research uses a qualitative descriptive type. The techniques and methods in this study use note taking techniques and the listening method in mentioning terms or conversations when the Kuih Ashura tradition is carried out by the Malay community of Nakhon Si Thammarat. This study seeks to explain that the Kuih Ashura tradition is always carried out every year in the Islamic New Year. The results showed that there were 12 monomorphemic forms, 9 polymorphemic forms, and 2 forms of Kuih Ashura culture in the Malay society of Nakhon Si Thammarat as ideas, values, norms, provisions, and as community activities.Keywords: The Kuih Ashura, Malay Society Thailand, Ethnolinguistic Study